BRD4 Inhibition Enhances Azacitidine Efficacy in Acute Myeloid Leukemia and Myelodysplastic Syndromes - Pericole, Fernando Vieira; Lazarini, Mariana; de Paiva, Luciana Bueno; Duarte, Adriana da Silva Santos; Vieira Ferro, Karla Priscila; Niemann, Fernanda Soares; Roversi, Fernanda Marconi; Olalla Saad, Sara Teresinha (Frontiers in Oncology, 2019)
Myelodysplastic syndromes (MDS) are clonal hematopoietic stem cell-based disorders characterized by ineffective hematopoiesis, increased genomic instability and a tendency to progress towards acute myeloid leukemia (AML). MDS and AML cells present genetic and epigenetic abnormalities and, due to the heterogeneity of these molecular alterations, the current treatment options remain unsatisfactory. Hypomethylating agents (HMA), especially azacitidine, are the mainstay of treatment for high-risk MDS patients and have been considered for elderly AML. The aim of this study was to investigate the potential role of the epigenetic reader bromodomain-containing protein-4 (BRD4) in MDS and AML patients. We identified the upregulation of the short variant BRD4 in MDS and AML patients, which was associated with a worse outcome of MDS. Furthermore, the inhibition of BRD4 in vitro with JQ1 or shRNA induced leukemia cell apoptosis, especially when combined to azacitidine, and triggered the activation of the DNA damage response pathway. JQ1 and AZD6738 (a specific ATR inhibitor) also synergized to induce apoptosis in leukemia cells. Our results indicate that the BRD4-dependent transcriptional program is a defective pathway in MDS and AML pathogenesis and its inhibition induces apoptosis of leukemia cells, which is enhanced in combination with HMA or an ATR inhibitor.